Using Superimposed Quantity Theory and Negative Sequence Network for Unbalanced Voltage Sag Source Detection - Kanokbannakorn, Weerawoot; Saengsuwan, Trin; sirisukprasert, Siriroj (Engineering and Applied Science Research, 2014)
This paper proposed a new algorithm to identify the unbalanced voltage sag source location using superimposed quantity theory and negative sequence. This algorithm is derived mathematically. The accuracy of model is verified by computer simulation and field test. The results demonstrate that the negative incremental impedance can effectively reveal sag source location and this algorithm can be applied to real power system.